First preliminary report on the project for a new Cushitic comparative dictionary - Blažek, Václav; Takács, Gábor (Lingua Posnaniensis, 2024)
The paper reports about the start of the joint research project by the two authors for the 4th attempt at composing the comparative dictionary of all Cushitic languages.